Buku Suplemen Literasi Ketahanan Pangan: Media Pembelajaran Keterampilan Menulis dalam Budaya Konsumsi Siswa SD - Puspita, Shahla Nadia; Istiq’faroh, Nurul; Setiyawati, Nur Syamsiyah; Aliyah, Nabila Nur (Jurnal Ilmu Sosial dan Budaya Indonesia, 2026)
This study was motivated by elementary school students’ limited understanding of healthy, high-quality food and the importance of food security in daily life. This study aims to develop and test the effectiveness of an informative text-based supplementary book on food security in improving student learning outcomes. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 24 fourth-grade students at UPT SD Negeri 219 Gresik. Data were collected through validation sheets, observations, and pre-test and post-test assessments. The validation results showed that the supplementary book received an average score of 4.39, categorized as highly suitable. The effectiveness test results indicated a significant difference between pre-test and post-test scores with a significance value of 0.000 (p < 0.05). The effect size of 1.568 falls into the large category, while the N-gain of 0.3098 falls into the moderate category. Thus, the developed supplementary book is deemed effective in improving students’ learning outcomes and literacy skills.